Behavioral, physiological, and cellular responses following trophic transfer of toxic monoaromatic hydrocarbons - Scarlett, Alan; Dissanayake, A.; Rowland, S.; Galloway, T. (Society of Toxicology and Chemistry (SETAC), 2009)
The trophic transfer of monoaromatic hydrocarbons to predatory organisms feeding upon contaminated marine animals is not well reported within the scientific literature. Branched alkylbenzenes (BABs) unresolved by gas chromatography have been reported to be principal toxic components of bioaccumulated hydrocarbons in the tissues of some wild mussel, Mytllus edulis, populations with poor health status. Mussels, M. edulis, contaminated with a commercial mixture of BABs were fed to shore crabs, Garcinus maenas, for 7 d, and effects upon the behavior, heart rate, hemolymph cellular viability, and immune response of the crabs were assessed. Accumulation of BABs in crab midgut gland tissue was quantified by gas chromatography-mass spectrometry, and the presence of BABs in crab urine was detected spectrophotometrically using ultraviolet fluorescence spectroscopy. Analysis of crab tissues and urine revealed a proportion of the BABs was transferred from the mussel tissues to the crabs, but the majority was not present 3 d after consumption of the mussels and may have been metabolized, excreted, or both. The results do not support the hypothesis that BABs are likely to be biomagnified, at least by crabs, in the marine environment. Alterations to measured cellular and physiological responses of crabs fed BAB-exposed mussels were not significant. Consumption of contaminated mussels was shown to cause highly significant abnormal behavior that, in the wild, may affect the feeding ability of crabs and make them more vulnerable to predation. © 2009 SETAC.